Guided tour to the antiquity's factory: sociology, tourism and authenticity - Guerreiro, Jorge Andre (2017)
Authenticity has been one of the most used words as well as one of the most discussed subjects in the Sociology of Tourism over the last four decades. Having experienced several changes in its meaning, the term has followed the overall progression of tourism studies - from the functionalist to the constructivist approaches, culminating in the postmodern and phenomenological turn. Yet, as a scientific concept, authenticity hasn't always been heuristic enough to support the empirical requirements of research, a trait that can be traced back to the philosophical influences of the word, resulting in its lack of a clear definition. This article critically reviews the abundant literature regarding the subject of authenticity in tourism, from its origins to the present, ending with recommendations to future uses.